What are the types of Learning Modality? (Docentes 2.0 Journal, 2017)
The constructive mental activity that the student puts into play this set of elements, develops around the content is configured, from this perspective, as a fundamental key to learning, and the quality of such constructive mental activity, therefore, is arranged as a fundamental key to the quality of learning: neither every activity that the student performs when learning entails constructive mental activity, nor all constructive mental activity is equally desirable or optimal for quality learning.
Keywords: types of Learning; Learning Modality